Theoretical computer science : introduction to automata, computability, complexity, algorithmics, randomization, communication, and cryptography - Hromkovic, Juraj (Berlin : Springer, 2010)
Juraj Hromkovic takes the reader on an elegant route through the theoretical fundamentals of computer science. The author shows that theoretical computer science is a fascinating discipline, full of spectacular contributions and miracles. The book also presents the development of the computer scientist's way of thinking as well as fundamental concepts such as approximation and randomization in algorithmics, and the basic ideas of cryptography and interconnection network design.
Introduction; Alphabets, Words, Languages and Algorithmic Problems; Finite Automata; Turing Machines; Computability; Complexity Theory; Algorithmics for Hard Problems; Randomization; Communication and Cryptography; References.
Includes bibliographical references and index.
Keywords: COMPUTER SCIENCE